2018
DOI: 10.3136/fstr.24.435
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of a Satiety-inducing Carbonated Beverage that Forms a Bubble-containing Gel in the Stomach

Abstract: We developed a beverage that forms a gel containing gas bubbles in the stomach and induces satiety. In a preliminary experiment, we confirmed that when a carbonated beverage containing any one of three types of ionic polysaccharides was mixed with artificial gastric juice, it resulted in the formation of a gel containing gas bubbles. Among the three types of polysaccharides referenced above, low methoxyl pectin (LM pectin) was identified as being the optimal for preparation of the test beverage in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although the experiment in this study was an in vitro experiment, it was possible to identify factors influencing the size of the bubble-containing gel and its volumeretention capacity in the stomach. This is the first case were able to find a pectin (Pectin B) that produced a larger-volume gel, with longer retention of the expanded volume, than the pectin (Pectin A) used in a previous study [10]. By using GDS, we were able to comprehensively identify an excellent type of pectin for gel formation.…”
Section: Factors Affecting the Gel Volume Immediately After The Reactionmentioning
confidence: 62%
See 2 more Smart Citations
“…Although the experiment in this study was an in vitro experiment, it was possible to identify factors influencing the size of the bubble-containing gel and its volumeretention capacity in the stomach. This is the first case were able to find a pectin (Pectin B) that produced a larger-volume gel, with longer retention of the expanded volume, than the pectin (Pectin A) used in a previous study [10]. By using GDS, we were able to comprehensively identify an excellent type of pectin for gel formation.…”
Section: Factors Affecting the Gel Volume Immediately After The Reactionmentioning
confidence: 62%
“…Among these, the human Gastric Digestion Simulator (GDS) [12][13][14] stalsis, and allows direct observation of the digestive process in real time. In vitro experiments using the GDS have confirmed that the bubble-containing gel formed by this beverage expanded to a significant degree and showed no disintegration even under the influence of peristalsis, and the volume decrease was suppressed [10]. It also confirmed that the gel volume changed dynamically.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…ISF and its control solution were prepared according to the methods reported by Domoto et al. with minor modifications ( 31 ). Citric acid monohydrate (200 mg), sodium hydroxide (400 mg), and LM pectin (1,850 mg) were mixed and dissolved in 43 ml of purified water.…”
Section: Methodsmentioning
confidence: 99%
“…However, this method restricts the experimental protocol to a larger size of experimental animals and use of anesthesia (26)(27)(28)(29)(30). In the present study, to expand upper gastrointestinal tract we used the carbonated solution containing low methoxyl (LM) pectin, named as inflating stomach formulation (ISF), which forms stable gel bubbles under acidic condition in the stomach and inflates the stomach in humans (Table 1) (31). We firstly examined whether ISF induces gastrointestinal distension, GLP-1 secretion, and vagal afferent activation.…”
Section: Introductionmentioning
confidence: 99%